Service Innovation in a Complex Service System: Public Transit Service Sustainability Business Cases. (15th June 2016) - Sebhatu, Samuel Petros; Johnson, Mikael; Enquist, Bo
Abstract: This paper seeks to assess and analyse service innovation in a complex service system, using a theoretical framework that comprises three key concepts: service innovation, complexity, and sustainability. Using two public transit cases, from Zurich and Singapore, this contribution describes the challenges associated with understanding service innovation in the complex public transit service system, according to its basis in social and environmental perspectives on sustainability. The findings affirm theoretical attempts to conceptualize service innovation and value co-creation in the service systems. By delineating the challenges of integrating sustainable thinking in complex service systems for service innovations and understanding the role of public transport services in an international context, this study makes an original contribution to research in services, sustainability, and complexity.